Protective Factors Against Psychological Distress Among Inpatients in Substance Use Treatment: A Cross-Sectional Study - Kari Bøhle; Eli Otterholt; Stål Bjørkly (SAGE Publishing, 2021)
Several studies have found co-occurrence between substance abuse and mental health problems, as well as an association between treatment retention and psychological distress. The aim of this study was to investigate the association of possible protective factors with psychological distress. The present study tested physical activity, self-esteem and sense of coherence, and psychological distress level among inpatients in substance use treatment. The study design was cross-sectional and multicenter. Patients (N = 167) were recruited in 2018 from 10 Norwegian inpatient facilities. They self-reported on 3 validated measurement instruments: Rosenberg Self-Esteem Scale, Antonovsky's Sense of Coherence Scale, and frequency of physical activity. The Hopkins Symptom Checklist-10 was used as an outcome variable of psychological distress. The associations were investigated with multiple linear and logistic regression methods. The results suggested that high self-esteem and sense of coherence were protective factors against high levels of psychological distress: self-esteem (β = −.39, P  < .001) and sense of coherence (β = −.352, P  < .001). The results offer support for a salutogenic approach in substance use disorder (SUD) treatment by enhancing individuals' protective factors to reduce psychological distress.